2020
DOI: 10.3389/fonc.2020.00017
|View full text |Cite
|
Sign up to set email alerts
|

Oncogenic Role of PVT1 and Therapeutic Implications

Abstract: PVT1, a long non-coding RNA has been implicated in a variety of human cancers. Recent advancements have led to increasing discovery of the critical roles of PVT1 in cancer initiation and progression. Novel insight is emerging about PVT1's mechanism of action in different cancers. Identifying and understanding the variety of activities of PVT1 involved in cancers is a necessity for the development of PVT1 as a diagnostic biomarker or therapeutic target in cancers where PVT1 is dysregulated. PVT1's varied activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 96 publications
0
49
0
Order By: Relevance
“…Our observation of the high expression of PVT1 and MYC in MM cells compared with normal plasma cells is consistent with those of previous studies [ 17 ]. Many studies have illustrated that PVT1 levels are higher in many cancers with an increased MYC expression than in normal tissues and are associated with a poor prognosis [ 16 , 23 , 24 , 25 ]. Tissue microarray analysis of primary tumors indicated a high correlation between PVT1 and MYC expression, providing strong evidence for cooperation between PVT1 and MYC in different human cancers [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our observation of the high expression of PVT1 and MYC in MM cells compared with normal plasma cells is consistent with those of previous studies [ 17 ]. Many studies have illustrated that PVT1 levels are higher in many cancers with an increased MYC expression than in normal tissues and are associated with a poor prognosis [ 16 , 23 , 24 , 25 ]. Tissue microarray analysis of primary tumors indicated a high correlation between PVT1 and MYC expression, providing strong evidence for cooperation between PVT1 and MYC in different human cancers [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results suggested that a high level of PVT1 might be associated with a prognosis of relapse and drug resistance. An association between high PVT1 expression and poor prognosis was reported in several cancers [ 16 , 23 , 25 ]. The involvement of PVT1 in resistance to anticancer drugs through several pathways was documented [ 24 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As indicated by a previous study, TUG1 is associated with HK2-mediated glycolysis in osteosarcoma [33]. LncRNA PVT1 plays an oncogenic role in multiple cancers [34]. The overexpression of PVT1 enhances glucose metabolism via modulation of the miR-497/HK2 axis in osteosarcoma [35].…”
Section: Glycolytic Enzyme and Lncrnamentioning
confidence: 65%
“…Non-coding RNAs (ncRNAs) are RNA transcripts from genes not encoding for a protein. 9 Murine NOP2 is homologous to yeast protein NOP2p and human NOP2 (also named NSUN1 or P120). 10 NOP2 belongs to the NOP2/SUN (NSUN) RNA-methyltransferase family, which includes six other members: NSUN2 through NSUN7.…”
Section: Introductionmentioning
confidence: 99%